Expression and Contribution of NLRP3 Inflammasome During the Follicular Development Induced by PMSG - Zhang, Zhenghong; Wang, Fan; Zhang, Yan (Frontiers in Cell and Developmental Biology, 2019)
Follicular development and following ovulation induced by luteinizing hormone (LH) surge are critical for ovarian functions, but the molecular mechanism regulating ovarian ovulation attracts more attention and remains mainly unknown. Recent researches on the nucleotide leukin rich polypeptide 3 (NLRP3) inflammasome shred light on it. Given pregnant mare serum gonadotropin (PMSG) can not only trigger the follicular development, but also induce the following ovulation, the present study therefore examined that expression and localization of NLRP3 inflammasome through immunohistochemistry and Western blotting during the follicular development induced by PMSG. The results showed expressions of NLRP3 and the adaptor protein apoptosis-associated speck-like protein (ASC) significantly increased in the outside of intrafollicular fluid, further analysis found that caspase-1 was activated and IL-1 production was also upregulated after 52h-treatment of PMSG. Furthermore, a significant increase of ovulation-related genes, hypoxia inducible factor (HIF)-1a and endothelin (ET)-1, was found after 52h-treatment of PMSG. To our knowledge, it is the first time to clearly indicated the activation of NLRP3 inflammasome may contribute to the ovulation of PMSG-treated ovaries, which will help to further clarify the ovulatory mechanism in mammals.